Poetic Improvisation: a Didactic Proporsal to Teach Costa Rican Contemporary Poetry on Secondary School - Venegas Carvajal, Steven (2022)
The following article consist to an investigation about didactics of literature whose main object is to elaborate a didactic proporsal to strengthen the linguistic, strategic and literary communicative competences of the high school student based on the semiotic analysis of the image in contemporary Costa Rican poetry (2010-2020). The methodology used consists of a case study applied to a ninth-grade student. The results point to a development of the student’s reading comprehension and oral literary creation skills.